INFLUENCE OF WORK DISCIPLINE, EDUCATION LEVEL AND INCENTIVES ON THE PERFORMANCE OF EMPLOYEES OF SECURITY UNIT MEMBERS AT PT BANK MANDIRI (Persero) Tbk, BATAM BRANCH - Aman Aman; Nandang Lesmana; Suyono Suyono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of the study was to look at the influence of work discipline, education levels, and incentives on employee performance. Respondents in this study were members of the security unit at PT Bank Mandiri (Persero) Tbk, Batam Branch. The population in this study was as many as 70 respondents. The samples in this study were determined using saturated samples, where all the populations in the study were sampled. The results of this study are that partial work discipline has a significant effect on employee performance, the level of education has a significant effect on employee performance, incentives have a significant effect on employee performance. Simultaneously, work discipline, education level, and incentives have a significant effect on employee performance. The R Square score in this study was 84.6%, this means that work discipline, education level, and incentives were able to affect employee performance by 84.6%, while the remaining 15.4% was influenced by other factors not included in the study